Women, Media, and Stereotyping in India - Roy Chowdhury, Debjani (Journal of Neonatal Surgery, 2025)
Both the woman and victimization are very strong relationships. With Development of human civilization, increased the exploitation of women. The woman's condition went from bad to worse. Without man, his existence, were deemed to be redundant. Towards the twenty-first century, the entire global scenario has changed. Today's Woman is strong. In male dominated society, women are always trampled. It's not from today; this century has been going on. Media’s role towards women is becoming the growing concern of the feminist writers, basically regarding participation, performance and portrayal of women. As societies entered the world of modernization, the role of women changed dramatically. Media played an important role in the modernization of societies and greatly affected the image of women in today’s modern world. Today, the role of women has changed. She has come out of closed rooms. Through this study, deals with this fast-changing role of women portrayed in Indian media and its influence on the Indian society with a focus on some representative incidents. The mass media, to raise women's issues; has been successful and unsuccessful both. With the evolving situation of women in India, has been study the role of media. Raising issues of women in the media have played a key role. The media, reports of female oppression, social consciousness, humanity, so many times in the sugar syrup wrapping sensation is, also introduced. Ever, his role was commendable; So many a times raise the finger on media. Through this research, has tried to understand; that What exactly, the media, women have been able to raise issues and how much. But if not, what was the cause. What is the solution of this problem? Connectedness is extremely main for women's process and accumulation media endeavor important part, in all spheres of existence, whether the controlling of aggregation growth disparity of literacy or raising the grade of history for vast people, women score a essential part to effort. In this environment, women know a Copernican persona to sport to create rousing in them to achieve their possible as they represent an indispensable enactment in effectively conveying substance that needs to be conveyed. It is lawful that media mortal brought to floodlighted, as never before, reliable misdemeanors against women but in a very subtle demean our, it also perpetuated the unimaginative person of women as a householder and an inconsequential entity in the traditional ideal method. By gradually constructive people persuasion, individualized beliefs and regularize grouping's ego perceptions, media influences the appendage of socializing and shapes ideology and mentation. A periodic gild is laden and processes with the group of the order